Difficult Decision on Tyroid Surgery of Expert Witness: Complication or Malpractice - Tümer, Ali Rıza; Yıldırım, Mahmut Şerif; Koçak, Savaş (The Bulletin of Legal Medicine, 2017)
Objective: Recurrent laryngeal nerve (RLN) paralysis and hypocalcemia following thyroid surgery have been designated as complication or malpractice. In this study, it was aimed to evaluate surgeons’ opinions towards RLN injury and hypocalcemia after bilateral subtotal thyroidectomy (BST) and total thyroidectomy (TT) in nodular goiter and thyroid carcinoma. Materials and Methods: We prepared a questionnaire to determine approaches of surgeons in such cases. We grouped the respondents according their thyroid surgery experiments and asked them to determine whether it is malpractice or complication in cases with unilateral or bilateral RLN paralysis and hypocalcemia after “bilateral subtotal thyroidectomy” and in cases with unilateral or bilateral RLN paralysis after “total thyroidectomy”. Results: In all groups describing bilateral RLN injury was more common. Problems which are defined as “complication” in cancer patients, were more likely defined as “malpractice” in benign cases. However, these differences were generally not statistically significant. Conclusion: There is no consensus about malpractice and complication discrimination among physicians. Every physician should evaluate every specific case in its own nature and conditions when asked to determine whether the case should be determined as complication or malpractice.